A systematic review of humanitarian operations, humanitarian logistics and humanitarian supply chain performance literature 2005 to 2016 - Banomyong, Ruth; Varadejsatitwong, Paitoon; Oloruntoba, Richard (Springer, 2019)
© 2017, Springer Science+Business Media New York.